Central nervous system post-transplant lymphoproliferative disorder after allogeneic hematopoietic stem cell transplantation: The Nagasaki transplant group experience. (2019) - Sakamoto, Hikaru; Itonaga, Hidehiro; Taguchi, Jun; Kato, Takeharu; Sawayama, Yasushi; Hayashi, Tomayoshi; Baba, Shiro; Moriuchi, Masako; Ohshima, Koichi; Yoshida, Shinichiro; Moriuchi, Yukiyoshi; Miyazaki, Yasushi
Abstract: A 17-year-old male received allogeneic transplantation for acute lymphoblastic leukemia, and presented with generalized seizures due to a solitary brain lesion with massive necrosis on day +621. Epstein–Barr virus (EBV) DNA copies were below the cut-off value in plasma. Stereotactic biopsy of the cerebral lesion confirmed the diagnosis of post-transplant lymphoproliferative disorder (PTLD) with large atypical cells positive for CD20 and EBER. In order to diagnose primary central nervous system PTLD, the biopsy should be applied as early as possible when brain lesion with necrosis develops in post-transplant patients regardless of EBV-DNA in plasma.